Benefits of Control, capital structure and company growth - Elisabeth Mueller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper studies the influence of the benefits of control on the capital structure and the growth of private companies for a sample of 8,964 UK companies with limited liability observed for up to 5 years. It is hypothesised that companies in which existing owners would lose more control if they expanded, have smaller equity increases, are more highly levered and grow more slowly. Potential loss of control is measured as the difference in the probability of winning a vote for the largest owner before and after a hypothetical equity increase. Evidence is found that is consistent with the hypotheses.
Older version: http://hdl.handle.net/10419/24147
Keywords: G32; M13; L20; 330; benefits of control; capital structure; company growth; small and medium-sized enterprises; Corporate Governance; Kapitalstruktur; Unternehmenswachstum; Großbritannien